On the Steinmanellidae (Bivalvia: Myophorelloidea); their palaeo-biogeography, evolution and classification - Cooper, Michael R.; Leanza, Hector Armando (Neues Jahrbuch für Geologie und Paläontologie - Abhandlungen)
The trigoniid group "Pseudo-Quadratae" was introduced for Cretaceous descendents of Myophorellidae with a convergent resemblance to Tethyan Quadratotrigoniinae (= Quadratae). Subsequently it was made the basis of the subfamily Steinmanellinae, which herein is elevated to family rank. The earliest record of the group is from the Early-Middle Kimmeridgian of the Tethyan Realm (American Province), from where it spread into the Boreal and Gondwanic realms. Steinmanellids rose to dominance in the cool temperate waters of the Andean Province, and the latter represents their centre of diversification. They are absent from the predominantly cold circum-polar waters of Southern and Eastern Gondwana, i.e.the Antarctic and Maorian provinces, as well as from the Australasian Province. The evolution of the group is tracked and two lineages identified, comprising 47 nominal species assigned to 14 genera, 9 of which are new: Stoyanowella, Philippiella, Garatella,Weaverella, Neuquenella, Pseudoyaadia, Popenoella, Louella, and Tashiroella. One lineage (Yaadiinae nov.) migrated northwards from its Tethyan origin into the Cordilleran Province of the Boreal Realm and thence, in the Late Cretaceous, to the Oriental Province, surviving in both biochores into the Maastrichtian. The second lineage, the subfamily Steinmanellinae, appeared in the Early-Middle Kimmeridgian of the American Province, but its centre of diversification was in the Andean Province where it appeared in the Early Tithonian and survived until the Late Hauterivian. From there it migrated eastwards into the Ethiopian Province, reaching as far as India, where it is recorded only from the Late Valanginian and Barremian. Fil: Cooper, Michael R. Universite de Rennes I; Francia Fil: Leanza, Hector Armando. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales Argentina